2004
DOI: 10.1002/cbdv.200490117
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Impact Assessment of Oil Pollution in Agbada West Plain of Niger Delta, Nigeria: Field Reconnaissance and Total Extractable Hydrocarbon Content

Abstract: Typical post-impact assessment of an oil-spill-impacted site in Agbada west plain of the Niger Delta basin of Nigeria was carried out 13 months after recorded incidence of spillage, using empirical indices of reconnaissance and extractable hydrocarbon content. Field-reconnaissance surveys revealed lower species' numbers and diversity of surface and subterranean flora and fauna. The presence and absence of such plant species as Elaeis guineensis, Musanga cecropiodes, and Andropogon gayanus, as well as animal sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 2 publications
1
43
0
Order By: Relevance
“…The presence of oil on the mangrove floor, for instance, will encumber the decay process of the litters from mangroves, which ordinarily enhance the accumulation of organic matter. Osuji et al, (2004) and many past studies on the Niger Delta have reported such higher than normal hydrocarbon concentrations in soils many months after oil spillage and have noted similar deteriorations of the mangrove system as a result of such spillages. Aside from the said fertility problems that are usually associated with contamination of the mangrove floor by spilled-oil, oiling of the mangrove system may also be accompanied with many other features such as leaf loss or complete defoliation of the flora from either root or leaf exposure to the oil especially in severely impacted areas; this includes the defoliation of the characteristic Rhizophora mangrove seedlings in affected areas (Ekweozor, 1998).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…The presence of oil on the mangrove floor, for instance, will encumber the decay process of the litters from mangroves, which ordinarily enhance the accumulation of organic matter. Osuji et al, (2004) and many past studies on the Niger Delta have reported such higher than normal hydrocarbon concentrations in soils many months after oil spillage and have noted similar deteriorations of the mangrove system as a result of such spillages. Aside from the said fertility problems that are usually associated with contamination of the mangrove floor by spilled-oil, oiling of the mangrove system may also be accompanied with many other features such as leaf loss or complete defoliation of the flora from either root or leaf exposure to the oil especially in severely impacted areas; this includes the defoliation of the characteristic Rhizophora mangrove seedlings in affected areas (Ekweozor, 1998).…”
Section: Discussionmentioning
confidence: 59%
“…This perhaps explains the defoliated state of some mangroves found at the study site (cf: Figs 2 and 3), especially those that were within the immediate vicinity of the right-of-way. High hydrocarbon content of soils has been known to affect soil physico-chemical properties, which in turn affect the agricultural potentials of such soils (Amadi and Dickson, 1993;Ezebuiro, 2004 andOsuji et al, 2004). Although soils of the mangrove floor under consideration may well be of limited cultivation value on account of the people's dual occupation in fishing and farming, the presence of such levels or range of hydrocarbons at the study site might severe agricultural productivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly in Nigeria, the detrimental effects of oil exploitation on the environment and the communities are well studied (for example, Aghalino, 2009;Anifowose et al, 2012;Ikelegbe, 2001;Obioha, 2009;Osuji et al, 2004). Given the significant revenues earned with oil and the persistent high levels of insecurity and urban poverty, oil has mostly become a "resource curse" for communities in rural Nigeria (Sala-i-Martin and Subramanian, 2013;Obi, 2012;Idemudia, 2012).…”
Section: Introductionmentioning
confidence: 99%